Sosialisasi Media Pembelajaran Interaktif Berbasis Digital Dalam Pembelajaran Bahasa Arab dan Pendidikan Agama Islam di SDN 02 Perumnas Way Kandis - Ajeng Rahmawati, Rima; Munawaroh (Al Mufid, 2024)
The socialization of interactive digital-based learning media is a strategic step to enhance the quality of teaching, particularly in Arabic Language and Islamic Education subjects at SDN 02 Perumnas Way Kandis. The school has committed to utilizing digital technology, but it still faces challenges in optimizing the application of interactive learning media. This community service activity aims to provide socialization and training for teachers to use interactive learning media more effectively. The main objectives of this activity are: 1) to socialize the use of interactive learning media to teachers, and 2) to assist them in integrating this technology into classroom learning processes. The participants of the training include 20 teachers of Arabic Language and Islamic Education subjects. The stages of the activity include administrative preparation, material presentation, practical use of the media, and evaluation of results. The evaluation was conducted descriptively to assess the success of the program. The results showed that the socialization and training were conducted successfully, with active participation from the teachers. The mentoring also succeeded in improving the teachers' understanding and skills in integrating interactive learning media into their teaching.